2009
DOI: 10.1073/pnas.0900638106
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of short transmembrane helices by the Sec61 translocon

Abstract: The insertion efficiency of transmembrane (TM) helices by the Sec61 translocon depends on helix amino acid composition, the positions of the amino acids within the helix, and helix length. We have used an in vitro expression system to examine systematically the insertion efficiency of short polyleucine segments (Ln, n ‫؍‬ 4 … 12) flanked at either end by 4-residue sequences of the form XXPX-Ln-XPXX with X ‫؍‬ G, N, D, or K. Except for X ‫؍‬ K, insertion efficiency (p) is <10% for n < 8, but rises steeply to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
127
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(140 citation statements)
references
References 28 publications
13
127
0
Order By: Relevance
“…In many cases, the TM topology of a signal sequence is likely to be determined within a short range. The positive charges flanking an H-segment enhance stop translocation (Jaud et al, 2009;Kuroiwa et al, 1990;Kuroiwa et al, 1991;Lerch-Bader et al, 2008). The TM topology is achieved as soon as the positive charges reach the translocon.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the TM topology of a signal sequence is likely to be determined within a short range. The positive charges flanking an H-segment enhance stop translocation (Jaud et al, 2009;Kuroiwa et al, 1990;Kuroiwa et al, 1991;Lerch-Bader et al, 2008). The TM topology is achieved as soon as the positive charges reach the translocon.…”
Section: Discussionmentioning
confidence: 99%
“…Accessibility of this segment in any orientation to the aqueous surface in the course of substrateinduced conformational changes should thus become detectable. Dyes at positions 22,23,26,27,28,32,33,34,35,42, and 45 cover the region from the hinge to the APH and an adjacent conserved negatively charged stretch. Position 51 served as positive control for quenching, as it is already positioned in an exposed region that is not anymore required for functionality (25).…”
Section: A Cell-growth Effect Of the Tata Membrane-anchor That Is Commentioning
confidence: 99%
“…Notably, a stretch of 12 hydrophobic residuesalthough very short -is sufficiently long for a complete membrane-integration of a peptide by the Sec61 translocon in eukaryotes (42).…”
Section: Substrate-inducedmentioning
confidence: 99%
“…Although hydrophobicity is the predominant factor (16), it is insufficient per se to determine whether or not a given polypeptide segment will be integrated into the membrane (17,18). Both residues immediately flanking a transmembrane (TM) segment (19) and those in other TM segments upstream or downstream (18,20) can also contribute to the membrane insertion propensity of the segment. Experiments have demonstrated that the polypeptide chain can interact with lipids while still in the channel (21)(22)(23), leading to the proposal that insertion is a thermodynamic partitioning between channel and membrane (23)(24)(25).…”
mentioning
confidence: 99%